(Bio)active Compounds in Daisy Flower (Bellis perennis) - Anna-Lena Albien; Timo D. Stark (Molecules, 2023)
The common daisy (Bellis perennis) belongs to the family Asteraceae and, in recent years, some new research has been published on the bioactive compounds and biological activities of its extracts. In 2014, the knowledge was partially summarized, but several new studies have been published in the last nine years. In addition, the substances were tabularly consolidated to give a comprehensive overview of over 310 individual components, compound classes, and bioactivities, as well as their accurate plant organ origin. The latest results have shown that the plant has antioxidative, antimicrobial, anticancerogenic, wound healing, antidepressive, anxiolytic, nephroprotective, and insulin mimetic effects, as well as an effect on lipid metabolism. Some studies in the field of homeopathy were also listed. Ideally, a biological effect and one or several compound(s) can be correlated. However, the compounds of the extracts used have often been qualified and quantified, but it remains unclear which of these substances have an activity. The works often stick at the level of the crude extract or a fraction, but not at a single purified and tested compound and, consequently, they are hampered by a missing comprehensive bioactivity workflow. This review provides a critical overview and gaps and offers a basis for further research in this area.